Long noncoding RNA expression signatures of bladder cancer revealed by microarray - ZHU, YI-PING (D.A. Spandidos, 2014)
Dysregulation of long noncoding RNAs (lncRNAs) has been regarded as a primary feature of several human cancers. However, the genome-wide expression and functional significance of lncRNAs in bladder cancer remains unclear. The aim of this study was to identify aberrantly expressed lncRNAs that may play an important role in contributing to bladder cancer pathogenesis. In this study, we described lncRNAs profiles in four pairs of human bladder cancer and matched normal bladder tissues by microarray. We finally determined 3,324 differentially expressed human lncRNAs and 2,120 differentially expressed mRNAs (≥2-fold change). A total of 110 lncRNAs were significantly differentially expressed between the tumor and the control groups (≥8-fold change). Four lncRNAs (TNXA, CTA-134P22.2, CTC-276P9.1 and KRT19P3) were selected for further confirmation of microarray results using quantitative PCR (qPCR), and a strong correlation was identified between the qPCR results and microarray data. We also observed that numerous lncRNA expression levels were significantly correlated with the expression of tens of protein coding genes by construction of the lncRNA-mRNA co-expression network. Kyoto Encyclopedia of Genes and Genomes annotation showed a significant association with p53, bladder cancer, cell cycle and propanoate metabolism pathway gene expression in the bladder cancer group compared with the normal tissue group, indicating that deregulated lncRNAs may act by regulating protein-coding genes in these pathways. We demonstrated the expression profiles of human lncRNAs in bladder cancer by microarray. We identified a collection of aberrantly expressed lncRNAs in bladder cancer compared with matched normal tissue. It is likely that these deregulated lncRNAs play a key or partial role in the development and/or progression of bladder cancer.